2021
DOI: 10.3847/2041-8213/ac1db5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Global Convective Dynamos with Mean-field Models: Full Spectrum of Turbulent Effects Required

Abstract: The role of turbulent effects for dynamos in the Sun and stars continues to be debated. Mean-field (MF) theory provides a broadly used framework to connect these effects to fundamental magnetohydrodynamics. While inaccessible observationally, turbulent effects can be directly studied using global convective dynamo (GCD) simulations. We measure the turbulent effects in terms of turbulent transport coefficients, based on the MF framework, from an exemplary GCD simulation using the test-field method. These coeffi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The product of the radial gradient of W and    = + determines the propagation direction of the dynamo wave in αΩ dynamos (Parker 1955;Yoshimura 1975). Figure 3(d) indicates both poleward ( ¶ W < 0 r ) and equatorward ( ¶ W > 0 r ) regions outside the tangent cylinder and predominantly poleward propagation in the lower part of the CZ inside the tangent cylinder.…”
Section: Flow States and Dynamo Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of the radial gradient of W and    = + determines the propagation direction of the dynamo wave in αΩ dynamos (Parker 1955;Yoshimura 1975). Figure 3(d) indicates both poleward ( ¶ W < 0 r ) and equatorward ( ¶ W > 0 r ) regions outside the tangent cylinder and predominantly poleward propagation in the lower part of the CZ inside the tangent cylinder.…”
Section: Flow States and Dynamo Considerationsmentioning
confidence: 99%
“…Neither of these possibilities can be ruled out immediately with the data at hand, although the shear near the surface is not very prominent in the current simulations. However, explanations based on such simple models should be considered with caution in light of a recent study by Warnecke et al (2021), who found that explaining the cause and evolution of large-scale magnetism in a spherical shell simulation required a mean-field model with 18 turbulent transport coefficients derived using the test-field method (e.g., Schrinner et al 2007).…”
Section: Flow States and Dynamo Considerationsmentioning
confidence: 99%
“…Non-linear feedback also occurs at small scale in dynamo action, and this aspect has been modeled as a simple alpha quenching in this work. Nevertheless, recent studies underline that mean-field coefficients can have non-trivial dependencies, for instance, in high Rossby regime where anti-solar DR are expected (see Warnecke et al 2021, and reference therein). Such complex feedbacks are beyond the scope of the present study and shall be considered in future works (see also Pipin 2021).…”
Section: Model Contextmentioning
confidence: 99%
“…Neither of these possibilities can be ruled out immediately with the data at hand, although the shear near the surface is not very prominent in the current simulations. However, explanations based on such simple models should be considered with caution in light of a recent study by Warnecke et al (2021), who found that to explanation the cause and evolution of large-scale magnetism in a spherical shell simulation required a mean-field model with 24 turbulent transport coefficients derived using the test-field method (e.g. Schrinner et al 2007).…”
Section: Flow States and Dynamo Considerationsmentioning
confidence: 99%